Parental Vaccine Hesitancy in a COVID-19 World: A Qualitative Study of Midwestern Parents’ Decisions Regarding COVID-19 Vaccination for Their Children : Parental COVID Vaccine Hesitancy - Beatty, Simon; Macke, Jamison; Griffin, Kellie; Villwock, Jennifer (Kansas Journal of Medicine, 2023)
Introduction. With the launch of the SARS-CoV-2 (COVID-19) vaccines, a new cohort of people exist who do not consider themselves to be totally vaccine-hesitant, but are specifically COVID-19 vaccine (CVH) parents. There is a need to learn from CVH parents, to ensure their concerns are addressed allowing them to comfortably vaccinate their children against the COVID-19 virus.Methods. Surveys were used to identify CVH parents. Via semi-structured interviews, we assessed the attitudes of CVH parents towards COVID-19 vaccination in children. An inductive coding method was used to analyze transcripts and develop themes.Results. Fourteen parents were interviewed. 50% (n=7) had received the COVID-19 vaccine even though they had doubts. Six reported that education about mRNA vaccine production was helpful in deciding to get vaccinated. Parents were reluctant regarding pediatric vaccination due to lack of long-term studies and concerns about adverse impact on childhood development. As opposed to public health leaders like the CDC and Dr. Fauci, personal physicians were the most trusted source of information and direct conversations with them were the most influential.Conclusions. Doctors are the most trusted source of information regarding the COVID-19 vaccine. Personal conversations with health professionals were the most influential factors in vaccine-hesitant individuals deciding to proceed with vaccination. Rather than broad public health messaging and advertising to increase rates of vaccination, these findings indicate that training for health care professionals in how to effectively counsel COVID-19 hesitant patients may be a high-impact area of opportunity to improve adherence to vaccine recommendations.